Host Manipulation by Parasites: Cases, Patterns, and Remaining Doubts - Heil, Martin (Frontiers in Ecology and Evolution, 2016)
Parasites must overcome host immunity and change hosts for dispersal. Therefore, seemingly odd behaviors of parasitized animals, like those exhibited by 'Zombie ants'¬ or the 'fatal attraction' of mammals to their predators, have been explained as the extended phenotype of parasites that manipulate their hosts for transmission enhancement. Manipulation has evolved in all major phylogenetic lineages of parasites but is not ubiquitous. In fact, the real frequency and relevance of manipulation is still matter of debate. Here, I highlight some of the most pertinent questions that arise if we aim at a broader understanding of the ecological relevance and evolutionary trajectory of manipulating parasites. Why are more parasites with a trophic mode of transmission manipulating their host than horizontally transmitted parasites? Why are the causal agents of sexually transmitted diseases (STDs) so rarely reported to manipulate their host? Why do parasites of animals usually manipulate their intermediate host, whereas many pathogens of plants manipulate their final host and then cause a 'fatal attraction' of herbivores to the already infected plant? How can we distinguish manipulation effects from adaptive host responses to parasitization? Does manipulation cause a cost to certain parasites that can select against the evolution of manipulation? More emphasis should be put on direct comparisons among parasites of animals, plants, and humans. Manipulation for transmission enhancement should be studied in concert with manipulation for host immunity suppression, the molecular mechanisms that control the manipulation effect need to be deciphered, and we should test for alternative explanations for the observed phenotypic changes. Finally, we should quantify transmission rates and net fitness for manipulating and non-manipulating parasites, in ecologically realistic setups, to identify the forces that select against the evolution of manipulation. Ultimately, parasite net fitness represents the relevant outcome of any manipulation effect.